Opening a window on probation cultures: a photographic imagination - Worrall, Anne; Carr, Nicola; Robinson, Gwen (Routledge, 2017)
Probation workers are among the least visible in the criminal justice system. Drawing on a pilot photographic project involving probation workers from several European countries, this chapter considers selected photographs and photo-elicitation data from England and Wales and Northern Ireland. It concludes that (amateur, democratized) photography has the potential to empower and give ‘voice’ to practitioners. Further, photo-elicitation suggests that photographs invoke imaginative debate about both the empirical realities and the normative dimensions of probation work and cultures.